Identifying non-breeding habitat conservation gaps of the critically threatened Spoon-billed Sandpiper (Calidris pygmaea) using species distribution model - Yifei Jia; Lili Sun; Jia Guo; Sicheng Ren; Hongyan Yang; Geng Huang; Li Wen; Neil Saintilan; Qing Chen; Yuyu Wang; Guangchun Lei (Global Ecology and Conservation)
The Spoon-billed Sandpiper (Calidris pygmaea) is one of the world's most critically endangered migratory shorebirds, facing severe threats along the East Asian-Australasian Flyway (EAAF). In recent years, many observations of this species were reported in new areas of southeast coasts in Asia, suggesting that there is large uncertainty in the current estimation of its nonbreeding habitats (i.e., staging and wintering grounds), presenting a knowledge gap for effective conservation. Using historical sightings collated from multiple sources, this study aimed to better understand the distribution of the shorebird’s suitable habitats by creating a random forest species distribution model utilizing landcover and topographic predictors. The predictions were then overlain with the current protection area network to identify gaps in conservation planning. Our results show that only 59 % of the suitable non-breeding habitats for Spoon-billed Sandpiper EAAF are located in the intertidal zone. Only 15 % of the predicted nonbreeding habitats are located within the current protection network. Moreover, we found that human disturbance pressure was high at both the protected and unprotected habitats. For suitable habitats outside protection areas, Thailand, Republic of Korea, and Bangladesh had highest human disturbance pressure. For suitable habitats within the current protection network, Democratic people’s Republic of Korea, Republic of Korea, and China had highest human disturbance pressure. Our results suggest that the staging sites along the Yellow Sea coasts and wintering grounds in the Thailand and Myanmar are the conservation priority areas, and management actions such as reducing human footprints in both protected and none-protected habitats, controlling the expansion of the invasive Spartina alterniflora, and maintaining tidal flats facing inundation by sea level rise are essential to sustain the population of this critically threatened shorebird.